COST-EFFECTIVENESS OF THE IMPLEMENTATION OF E-DEMOCRACY AND CIVIC TECHNOLOGIES FOR LOCAL DEVELOPMENT - BOHACH, Yurii; MARHASOV, Dmytro (Herald of Khmelnytskyi National University. Economic sciences, 2025)
In the era of digital changes and technological renewal of society, e-democracy tools and civic technologies are becoming increasingly important, contributing to increasing transparency, accountability of the authorities and involving citizens in decision-making processes at the local level. The introduction of tools such as electronic petitions, online voting, digital platforms for participation in budgeting and public discussions opens up new opportunities for intensifying civic participation and building partnerships between the government and the community. Given the limited financial resources of local governments, it is important to assess the economic effectiveness of such digital initiatives. It is equally important to investigate the extent to which e-democracy tools contribute to cost optimization, improved management decisions, and sustainable local development. The relevance of the topic is also due to the need to find effective models of community management in the context of decentralization and public power reform in Ukraine. Electronic services and participatory technologies are becoming not only a means of communication, but also a strategic resource for increasing trust in local authorities, attracting investments, and increasing the competitiveness of territorial communities. The study of the economic efficiency of the implementation of e-democracy tools is extremely relevant and has both theoretical and practical significance for local governments, the public and the scientific community.In the process of decentralization and strengthening the role of local self-government, the issue of increasing the efficiency of management of the development of territorial communities is of particular relevance. One of the modern tools that contributes to this is e-democracy, a system of mechanisms for digital interaction between the government and citizens, which ensures transparency, accountability and participation of the population in decision-making. At the same time, civic technologies also play an active role in this), which encompass digital platforms, services and tools to simplify citizens' participation in public life.The purpose of this study is to increase the openness of government, strengthen the participation of citizens in decision-making and ensure the sustainable development of territorial communities, the task of assessing the economic efficiency of the implementation of appropriate digital mechanisms is urgent.In the period of modernization of public administration through digital tools, the key role is played by the introduction of e-democracy tools and civic technologies, which create conditions for the active involvement of the population in governance processes and ensure the transparency of the functioning of authorities and the formation of an effective model of interaction between citizens and the state.Electronic democracy (e-democracy) is a modern form of implementing democratic processes through digital information and communication solutions. This technology includes digital tools that ensure citizen participation in decision-making, access to public information, communication with authorities, control over the activities of officials and organization of public initiatives.The introduction of e-democracy tools and civic technologies in the activities of local administrative bodies is not only a manifestation of the democratization of management processes, but also an important factor in increasing the economic efficiency of local development. The analysis confirms that with proper technical, organizational and regulatory support, digital tools contribute to cost optimization, increased transparency of resource allocation, reduced administrative burden and citizen involvement in decision-making. In addition, such technologies contribute to increasing public trust in local authorities, intensify civic participation and form a culture of open governance. This, in turn, leads to better management decisions focused on the real needs of the community, which allows for more efficient use of financial and material resources. In the long term, this ensures budget savings, reducing social risks, increasing the investment attractiveness of territories and generally strengthening the institutional capacity of local self-government.
Keywords: e-democracy; civic technologies; digital participation; local self-government; territorial communities; economic efficiency; public administration